Avaliação do nível de estresse e atividade física de professores de uma escola estadual - Hörner, Andreas (2021)
The teaching profession is considered by the International Labor Organization (ILO) to be one of the most stressful.Teachers face work overload, which generates illness due to occupational stress, high levels of anxiety and low quality of life. The aim of this study was to assess the level of occupational stress and physical activity of teachers at a state elementary and high school in the interior of Rio Grande do Sul. A cross-sectional, quantitative-descriptive study was carried out between June and July 2019. The inclusion criteria were all 78 teachers who exercised teaching activity at that school, in the three working shifts. In the exclusion period, teachers were away from work, on vacation, and who did not complete the questionnaires adequately or refused to complete them. Three data collection instruments were used, self-completed by teachers: a biosocial questionnaire (gender, marital status, children, willingness to work, intention to leave the profession, age, workload, teaching experience time, number of students who contacts daily), developed specifically for this study. For the assessment of the stress level of each teacher, the work stress scale (TSE) was used, validated by PASCHOAL and TAMAYO, 2004 and for the physical activity levels of the teachers, the International Physical Activity Questionnaire - IPAQ version short, initially proposed by WHO in 1998, and translated and validated in Brazil by Matsudo et al., 2001. It was approved by the Research Ethics Committee of the Federal University of Santa Maria (UFSM) with opinion number 3.326.165 / CAAE 08034819.8.0000.5346. The data were analyzed using descriptive statistics. Of the 53 teachers who were able to include the data, 72% were female, with an average age of 45.44 years, 50.94% were married and 39.62% taught two shifts at school. Regarding education, 66.04% of these teachers had a postgraduate course and 33.96% only undergraduate. The majority (75.47%) gained weight whose average was + 6.80 kg, however 54.72% stated that stress was not the responsible factor. 60.38% said they work at their best, 100%, like working at school, but 13.21% intended to leave school and 15.09% intended to leave the teaching profession. 54.72% of teachers have already taken sick leave. In the present study, all teachers had some level of stress, with the majority being 48 (90.47%) medium level of stress and 5 (9.43%) low level. With reference to physical activity, 86.79% (46 of 53) of the teachers in this study were active and 13.21% (7 of 53) sedentary. We concluded in this study, that although all the teachers said they like to work in this state school, everyone has occupational stress. As the majority belong to the female gender, we suggest, in this group, association with stress factors of the woman's double journey, represented by the education of children and school work, in addition to the low remuneration and increasing devaluation of the teaching career. As a small index of sedentary lifestyle was found, there should be no relationship with stress. The number of teachers in our research was a limitation of this study. There are few studies in the national and international literature on the topic addressed in this study, which we also consider another limitation.